The culture of methodological practice and the use of the method in the social sciences - makhlouf, boumediene (Journal of Social Sciences and Humanities, 2022)
The scope of accurate contemplation within the social sciences field in all its perspectives and specializations, especially since the beginning of the 20th century - it is noted that it has reached a significant stage of development, specialization, professionalism and maturity, which made it accede to the rank of the basic reference model or (paradigm). The methodological practice and curriculum within the field of social sciences are considered among the methodological and instrumental pillars utilized in understanding, interpreting, and framing the phenomenon as well as among the mechanisms of academic inferential treatment to achieve knowledge. The scientific and practical outputs of methodological practice and the use of the method in social sciences can be summed up at the level of the practical wings: (Alienation), (construction), (examination); and phased wings: (starting question), (survey), (problematic), (construction of analysis method). ), (Examination ), (information analysis), (verification).